The role of chatbots and virtual assistants in enhancing tobacco cessation counselling - V, Deepika; Jodalli, Praveen S.; B R, Avinash (Frontiers in Digital Health, 2025)
Tobacco remains one of the leading global public health threats, causing over 8 million deaths worldwide each year. Existing tobacco cessation strategies must be complemented with innovative approaches to enhance their effectiveness. This paper is intended to review the state and success of chatbots and virtual assistants in the delivery of tobacco cessation counselling services. Comprehensive literature search was performed on various databases including PubMed, SCOPUS, EMBASE, COCHRANE Library, and ScienceDirect using relevant keywords concerning tobacco cessation as well as artificial intelligence. The review is limited to studies published between March 2015 and March 2024 examining only the role of chatbots and virtual assistants in smoking cessation. The analysis of 31 studies found that chatbots and virtual assistants deliver continuous support, personalized interaction, and increased accessibility, which collectively boost user engagement. Their anonymity from other means of online counselling has significantly increased the willingness of people who want to stop smoking. The development of information technology has led to the advent of AI-based chatbots and virtual assistants as a promising novel tool for the tobacco cessation process, providing personalized, adaptive, and scalable support to web-based users. Personalized approaches improve the chances of success in quitting smoking and represent a major advancement of cessation strategies.